Technology Acceptance Model, Halal MSMEs Intention in Using QRIS - Pradesyah, Riyan; Khairunnisa, Khairunnisa; Ismail, Abdul Hadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The use of QRIS in the payment system used by halal MSMEs, there are still many limitations and problems that often arise, so in this case, researchers try to construct the Technology Acceptance Model theory, and Theory of Planned Behaviour, which aims to see the extent of its influence on the intensity of halal MSMEs in using QRIS. This research is quantitative research, with the SmartPLS analysis tool. The object of research is Halal MSMEs in the city of Medan. The questionnaire distribution uses two methods, namely online and offline. As for what is obtained, the X1 variable (Technology Acceptance Model) has a non-significant effect on variable Y (MSME intensity using QRIS) is 1.476 or 14.76%. Then the X2 variable (Theory of Planned Behavior) has a significant effect on Y (Intensity of halal MSMEs using QRIS) is 7,245 or 72.45%.